PEMBELAJARAN INOVATIF: KOMPETENSI MAHASISWA DALAM METODE KASUS DAN PEMBELAJARAN PROYEK BERBASIS TIM - Farida Fitriani; Wiwien Kurniawati; Menik Aryani (Comm-Edu (Community Education Journal), 2026)
This research aims to implement a learning model based on the case method and team-based projects in the Indonesian Language course to assess student competencies. The study applies a quantitative approach with a descriptive method, which seeks to provide a real picture of students' soft skills and hard skills. The research population consists of semester 1 students at Poltekkes Mataram, with data collection techniques including document study, questionnaire completion, and observation. The emerging data will be developed into self-assessment and peer-assessment instruments. The research instruments are designed based on aspects of soft skills and hard skills within the case method and team-based learning model, using a Likert scale to evaluate Poltekkes Mataram students' competencies. The results show that hard skills are higher, with an average score of 86 categorized as very good, covering data collection, report preparation, academic writing, data visualization, and referencing skills. Meanwhile, soft skills average 83.9, categorized as good, encompassing five key aspects: communication, critical thinking, problem-solving, collaboration, and leadership.